(untitled) (Research, Society and Development, 2022)
The housing projects is the way most used by the Brazilian federal government to attend the housing demand of the low-income population. The low quality in the production process leads to a greater need for maintenance, which becomes critical due to the limited availability of resources for residents, influencing user satisfaction. In this context, this study aimed to compare the survey of data obtained in 2010 in the INQUALHIS project on pathological manifestations in newly built housing projects with the surveys of pathological manifestations carried out in 2016 and 2019 of the same housing projects, analyzing the evolution of the state of conservation of the facades. The housing complexes presented problems related to use and lack of maintenance. This study, in addition to serving to detect the pathological manifestations of the objects of study, verified the post-occupancy evaluation - higher incidences of pathological manifestations, led to greater dissatisfaction of residents with the facades of buildings due to their bad appearance. In addition, observing the types of manifestations incident on the facades of both surveys, it was possible to perceive that the survey carried out in the newly built projects already revealed a predisposition of the most incident types in each set.